2013
DOI: 10.5539/elt.v7n1p159
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Reduced Forms Instruction on EFL Learners’ Listening and Speaking Abilities

Abstract: Listening comprehension is usually considered as one of the most difficult language skills to EFL learners due to the unavoidable presence of "reduced forms" in authentic speech. This study was an attempt to investigate the effect of explicit "reduced forms" instruction on Iranian EFL learners' overall listening comprehension and their ability to recognize and produce them in their daily conversations. The participants of this study were 50 intermediate English learners who were randomly assigned as the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The results are also in line with Mhammad Saber Khaghaninezhad & Ghasem Jafarzadeh [17] who determined that teaching "reduced forms" helped students to master their listening and speaking skills. There was a significant difference between two groups after treatment.…”
Section: Discussionsupporting
confidence: 85%
“…The results are also in line with Mhammad Saber Khaghaninezhad & Ghasem Jafarzadeh [17] who determined that teaching "reduced forms" helped students to master their listening and speaking skills. There was a significant difference between two groups after treatment.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, other research (e.g. Baghrahi et al, 2014;Khaghaninezhad and Jafarzadeh, 2014) also confirmed that teaching connected speech aspects significantly raised the students' awareness of those aspects in listening.…”
Section: Discussionmentioning
confidence: 67%
“…The results revealed that integrating authentic assessment into EFL classrooms can enhance oral communication and reduce anxiety among FL learners. Khaghaninezhad & Jafarzadeh (2014) investigated the effect of explicit reduced forms instruction on Iranian EFL learners' overall listening comprehension and their ability to recognize and produce them in their daily conversations. The participants were (50) intermediate English learners and were divided into an experimental group and a control group.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In addition, it is a vital skill in all areas of academic life. Effective listening is required for higher education students to understand formal lectures and tutorials, as well as to interact with other students in small groups, in project work, and in social situations (Khaghaninezhad & Jafarzadeh, 2014, Picard &Velautham, 2016.…”
Section: Introductionmentioning
confidence: 99%